We need to multiply each equation by different factors so that the coefficients next to the x-variable in each new equation are opposite numbers.
Multiplying the first equation by -4, we get:
![\begin{gathered} 5x-4y=60\text{ (eq. 1)} \\ (-4)\cdot(5x-4y)=(-4)\cdot60 \\ (-4)\cdot5x+(-4)\cdot(-4y)=-240\text{ Distributing} \\ -20x+16y=-240\text{ (eq. 3)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hk2p4bi87apvswzxkmq4xy7uxfbgf6e1qe.png)
Multiplying the second equation by 5, we get:
![\begin{gathered} 4x+5y=60\text{ (eq. 2)} \\ 5\cdot(4x+5y)=5\cdot60 \\ 5\cdot4x+5\cdot5y=300\text{ Distributing} \\ 20x+25y=300\text{ (eq. 4)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bdtqc6u7u9qos4syk9ma2bbuy4tmakki5y.png)
And now, the coefficients of the x-variable of equations 3 and 4 are -20 and 20.